Development and Optimization of a Super Saturable Self-Nanoemulsifying Drug Delivery System for Ibrutinib: Enhancing Solubility and Anticancer Potential - Parigela, Vyshali; Arumugam, Vijayalakshmi (Indian Journal of Pharmaceutical Education and Research, 2026)
Aim: This study explores the development and optimization of a Super saturable Self-Nanoemulsifying Drug Delivery System to enhance the solubility, bioavailability, and anticancer efficacy of ibrutinib. Materials and Methods: Saturation solubility studies identified Kolliphor® RH 40, castor oil, and PEG-600 as the optimal surfactant, oil, and co-surfactant, respectively. Formulation optimization was performed using a Box-Behnken design, with droplet size and encapsulation efficiency as key response variables. Characterization included particle size analysis, zeta potential, FTIR, DSC, and XRPD studies, while in vitro drug release was assessed through diffusion studies. The MTT assay on MCF-7 and PANC-1 cell lines evaluated the cytotoxicity and therapeutic potential of the formulation. Results: The optimized S-SNEDDS for Ibrutinib demonstrated favorable characteristics, including a small droplet size (71.12-76.38 nm), high encapsulation efficiency (61.56-87.22%), and stability under stress conditions. The formulation exhibited rapid drug release, with over 50% of Ibrutinib released within 240 min. Characterization studies, including FTIR and DSC, confirmed the amorphous nature of the encapsulated drug. Kinetic studies suggested a zero-order drug release mechanism. Cytotoxicity evaluation via MTT assay indicated that the nanoformulation had lower cytotoxicity on MCF-7 and PANC-1 cells compared to pure Ibrutinib​. Conclusion: These findings underscore the potential of S-SNEDDS as a promising approach to enhance the oral bioavailability of poorly water-soluble drugs like ibrutinib.
Keywords: Super saturable SNEDDS; Ibrutinib; Box-Behnken design; Nanocarriers; Drug; solubility; Cytotoxicity; Cell lines